Portfolio Assessments for Problem Based Learning Courses - Jartarghar, Uday; Hegade, Prakash; Shettar, Ashok (Journal of Engineering Education Transformations, 2025)
Problem-Based Learning is a student-centered teaching and learning pedagogy proven to be effective and applicable for wide range of domains. Problem based learning supports several forms of assessments like project work, casestudies, and reflections, all of them with the objective to improve problem solving, critical thinking and self-directed learning. Portfolios can be yet another way of supporting and designing assessments. This study proposes a research question to understand the impact of portfolio creation as an assessment method within Problem-Based Learning pedagogy and assesses its impact on students understanding and application of theoretical concepts in real world scenarios. With Reflective- Practice theory as conceptual framework, this work evaluates the effectiveness of the portfolios applied on a domain-based case study. Multi method was used as a research methodology for the study and self-selection was used as sampling technique for quantitative and qualitatively analysis respectively. The context of the study was VI semester algorithmic course students offered to students of circuit branches. Students were given several domains to create portfolios on and GitHub pages were used for the purpose. Students were guided with step wise process to create the portfolios. Scores of 83 students and interviews of 12 students were used for data analysis. With appropriate descriptive measures, statistical methods correlations, heat maps, student feedbacks, in-vivo coding and process coding, the collected data was analyzed for results and discussion. The results positively align towards the conclusion that portfolios can be an effective assessment method.